Zagadnienia holizmu w kontekście relacjonizmu i strukturalizmu - Luty, Damian (Hybris, 2016)
Two positions in which the mode of existence of Spacetime is considered are reconstructed — relationism and structuralism (I discuss the version of structuralism one can find in the so-called Ontic Structural Realism). I present and describe the notion of gravitational nonlocalities, at which one arrives through the difficulties with formulating laws of energy conservation in General Relativity. I state and try to defend a thesis, that the above difficulty may rise two different „weak” holisms on the ground of each mentioned position.